Draft 8th Five Year Plan (1990-95) and Annual Plan 1991-92 Leh District - Planning Commission (Planning Commission, 1990)
The approved outlay for the Annual Plan 1990-91 is Rs. 1288.00 lakhs which includes Rs. 313.44 lakhs as the Revenue component and Rs. 974.56 lakhs as the Capital component. An amount of Rs. 212.00 lakhs out of the total Revenue component of Rs. 423.00 lakhs of the 7th Five year Plan was transferred to the Non-Plan during 1990-91.
Leh District